Fast-track Surgery for Gastroenteric Neoplasms: A Meta-analysis. Issue 5 (September 2014) - Shao, Yi; Zou, Ling-Lin; Zhou, Qing-Hua; Zhong, Dian-Sheng; Guo, Feng-Jie; Ma, Li
Aims and Background: Fast-track surgery has been shown to enhance postoperative recovery. The objective of the study was to determine the differences of fast-track surgery and conventional care for patients with gastroenteric neoplasms. Methods and Study Design: We searched PubMed, EMBASE, and the Cochrane Library for related trials to compare hospital stay and rates of complications and readmission. Results: Thirteen randomized controlled trials, with 1, 962 patients, were included. Results showed the length of hospital stay was significantly reduced in the fast-track group. The complications rate was lowered in colorectal surgery. There were no significant differences in rate of readmissions. Conclusions: Current trials show that fast-track surgery may reduce the length of hospital stay and lower the rate of complications of gastroenteric surgery.